LYCIUM BARBARUM AND SPERM DNA INTEGRITY: A NARRATIVE REVIEW OF ANTIOXIDANT MECHANISMS AND LIMITED CLINICAL EVIDENCE (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize mechanistic and clinical evidence on Lycium barbarum in relation to sperm DNA integrity, with emphasis on oxidative stress and the testicular microenvironment.Methods: A structured narrative review was conducted using PubMed/MEDLINE, Web of Science, Scopus, and Google Scholar up to November 2025 with keywords related to Lycium barbarum, Lycii Fructus, Lycium barbarum polysaccharides, oxidative stress, sperm, testis, sperm DNA damage, and male infertility.Results: Ten key references were synthesized, including one mechanistic review, eight preclinical studies, and one randomized placebo-controlled trial. Preclinical evidence showed that Lycium barbarum polysaccharides increased antioxidant enzyme activity, reduced lipid peroxidation, preserved seminiferous tubule structure, supported Sertoli cells, and modulated pathways related to apoptosis, endoplasmic-reticulum stress, and iron-dependent injury. However, direct evidence on sperm DNA fragmentation remained limited. The only clinical trial reported improvements in oxidative stress, testosterone, and semen quality, but did not directly assess sperm DNA damage or reproductive outcomes.Conclusion: Lycium barbarum has a plausible biological basis for supporting sperm DNA integrity, but human evidence remains very limited and is insufficient for routine recommendation. Further randomized trials using standardized preparations and direct measures of sperm DNA damage are required.
Keywords: Lycium barbarum; goji berry; sperm DNA integrity; oxidative stress; male infertility.